Documentación cinematográfica digital: el gestor digital - Cuadra Colmenares, Elena de la (Documentación de las Ciencias de la Información, 2006)
Elaborating any film product involves the work of a large number of professionals of different backgrounds. As the author sees it, this process requires an Information Science professional to attend their professional needs, which are threefold. Firstly, film professionals need to obtain specific information; secondly, they need that information to be well managed; and finally, they need document circulation to be assessed by a professional who will ensure technical quality –always in digital format. An Information Science Professional, will answer these needs, thus adopting a threefold role of documentator, manager and digital manager.
Keywords: Film Documentation; Digital Manager